PEMBELAJARAN IPS BERBASIS MULTIPLE INTELLIGENCE UNTUK PENINGKATAN KOMPETENSI INTELEKTUAL DAN SOSIAL - Zainul Mubtadiin; Darsono Darsono; Herpratiwi Herpratiwi (Faculty of Teacher Training and Education, University of Lampung, 2013)
Lack of intellectual and social competence of students form the basis of this research. This research aims to analyze the social studies learning based multiple intelligence in improving students' intellectual and social competence eighth grade junior Darul Ulum Sekampung. The approach of this study is action research with three cycles. The first cycle with PPKB-Cooperative Learning Models, The Second cycles with PPKB-CTL models, and the third cycles with PPKB-dramatic models. The data collection tool include: testing, observation and questionnaires attitude. Data were analyzed by descriptive qualitative. Results of this study show that there is an increase of 91% intellectual competence and there is an increasing social competence as big as 88% to 91% consistency in cycle three. Keyword: multiple intelligence, kompetensi intelektual, sosial